Hamoraon, Hagabeoan, Hasangapon: Konsep dan Pengaruhnya Bagi Pembentukan Karakter Masyarakat Batak Toba - Simamora, Chandra Susilo; Marbun, Kembarto; Simanjorang, Sandro (Perspektif, 2015)
The article tries to argue the so-called three philosophical values of life ofthe Toba people (Batak Toba people) of North Sumatra. These three philosophicaldimensions, namely hamoraon (wealth), hagabeon (discendant) andhasangapon (honour), are regarded powerfully determine the people’s character.Throughout their life, the people are strongly influenced by as well asdirected their own life to achieve the three fundamental values. The writers,however, are convinced that a superficial understanding upon this philosophyof life could unfortunately bring the people of Batak Toba to an idea thattheir very life is simply chasing honour, power, and wealth.